Bioefficacy and Infection Mechanism of Several Entomopathogenic Fungi on Crocidolomia Binotalis Zell - Hashim, Norzita (2000)
The role of entomogenous fungi as natural enemies for cruciferous insect pests has recently been explored and several siolates of hypomycetous fungi have been dientfiied. The ability of three entomopathogenic siolates of Beauveria bassiana (Bals). Vuill, Paecilomyces fumosoroseus (Wize) Brown and Smith and Metarhizium anisopliae var. majus (Metsch). Sorokin to cause infection against second instar larvae of Crocidolomia binotalis Zeller was tested. Dosa ge-response assays were conducted in an ambient environment of 28 ± 2° dark peroids. treatment. Results indicated that all isolates of the entomopathogenic fungi were able to cause mortality on the second instar larvae of C. binotalis. Exposure to sprays of a conidial suspensoin of varying dosages from 20 ml to 2 x 10 7 larval mortality from 10 0. to 100.00/0 conidia ml-1, larval mortality was recorded in excess of 80 %.